2013
DOI: 10.1073/pnas.1208524110
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a cooperates with canonical Wnts to generate midbrain dopaminergic neurons in vivo and in stem cells

Abstract: Wnts are a family of secreted proteins that regulate multiple steps of neural development and stem cell differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(123 citation statements)
references
References 64 publications
(109 reference statements)
7
115
1
Order By: Relevance
“…The hESC-derived NPCs by FGF2 and/or SB431542 treatments are marked with forebrain characteristics and show the multipotent competence to form specific neurons (5,13,43). Canonical Wnt signal is a developmental patterning factor to caudalize anterior neurons and to specialize midbrain neuron formation (2). This Wnt signal in hESC-derived NPCs is antagonized by the endogenous DKK1 expression, and the attenuated Wnt activation consequently renders the establishment of anterior neuroectoderm bias (14).…”
Section: Discussionmentioning
confidence: 99%
“…The hESC-derived NPCs by FGF2 and/or SB431542 treatments are marked with forebrain characteristics and show the multipotent competence to form specific neurons (5,13,43). Canonical Wnt signal is a developmental patterning factor to caudalize anterior neurons and to specialize midbrain neuron formation (2). This Wnt signal in hESC-derived NPCs is antagonized by the endogenous DKK1 expression, and the attenuated Wnt activation consequently renders the establishment of anterior neuroectoderm bias (14).…”
Section: Discussionmentioning
confidence: 99%
“…While Wnt-3a has been described as canonical, Wnt-5a is generally associated with noncanonical Wnt signaling [49], and Wnt-7a is frequently found to play both canonical and noncanonical roles [50 , 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 51]. Bearing in mind that all these Wnts are required for the correct formation of the nervous system, and also that they often cooperate with one another [52], finetuning of canonical and noncanonical Wnt signals is likely to be necessary for neuronal development. In keeping with this, Wnt1/5a double KO (DKO) mice show exacerbated loss of dopaminergic neurons, when compared to Wnt5a KO mice, as described by Andersson et al [52].…”
Section: Wnt Signaling In the Mouse Brain: Wnt Ligands And Receptorsmentioning
confidence: 99%
“…Bearing in mind that all these Wnts are required for the correct formation of the nervous system, and also that they often cooperate with one another [52], finetuning of canonical and noncanonical Wnt signals is likely to be necessary for neuronal development. In keeping with this, Wnt1/5a double KO (DKO) mice show exacerbated loss of dopaminergic neurons, when compared to Wnt5a KO mice, as described by Andersson et al [52]. This elegant study also showed that mouse stem cells treated with both Wnt-3a and Wnt-5a produced more dopaminergic neurons, than cells treated with a single Wnt, providing further evidence for cooperation between noncanonical and canonical Wnts during dopaminergic differentiation, as suggested in an earlier study by the same group [53].…”
Section: Wnt Signaling In the Mouse Brain: Wnt Ligands And Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurr1 is a potential susceptibility gene for PD [166]. All these observations led to the hypothesis that activating Nurr1 in degenerating DA neurons might delay or modify the disease progression [167]. A synthetic low molecular weight Nurr1 activator named SH1, which increases the transcription of Nurr1, has been tested in a lactacystin-induced nigro-striatal degeneration model in mice [60].…”
Section: Nurr1 Activatormentioning
confidence: 99%